2000
DOI: 10.1136/jnnp.68.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of elderly patients with asymptomatic meningiomas

Abstract: AbstractsObjective-For the treatment of elderly patients with asymptomatic meningiomas, it is important to determine their natural history. Based on results of follow up examinations, the natural history of such patients was clarified and prognostic factors concerning the potential of tumour growth in the aged were identified. Methods-The clinical records and imaging studies of 40 elderly (over 70 years) patients with asymptomatic meningiomas were analysed. The patients were followed up with repeated imaging s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
1
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(102 citation statements)
references
References 20 publications
5
91
1
5
Order By: Relevance
“…However, the risk of surgical treatment must be balanced against the morbidity due to tumor growth that is associated with a conservative treatment. Previous studies have investigated the natural history of intracranial meningiomas (26)(27)(28)(29)(30). The growth rate of intracranial meningiomas has been reported as 2.4-5.3 mm per year (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the risk of surgical treatment must be balanced against the morbidity due to tumor growth that is associated with a conservative treatment. Previous studies have investigated the natural history of intracranial meningiomas (26)(27)(28)(29)(30). The growth rate of intracranial meningiomas has been reported as 2.4-5.3 mm per year (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the natural history of intracranial meningiomas (26)(27)(28)(29)(30). The growth rate of intracranial meningiomas has been reported as 2.4-5.3 mm per year (27)(28)(29). Other studies have reported that hyperintensity on T2-weighted imaging, a non-skull base location and the absence of calcification on imaging are considered positive indicators of tumor growth in intracranial meningiomas (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Among the several methods that have been previously used to evaluate the size of meningiomas by computed tomography (CT) or magnetic resonance imaging (MRI), the maximum diameter has been used to analyze the natural history of meningiomas (5)(6)(7)(8)(9). It is the simplest procedure; however, it is uncertain whether the maximum diameter accurately reflects the real volume of the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…The mean age of patients in these nine studies with growing tumors was 59.74 ± 0.15 years (range of 17 to 83 years) while the mean age of patients with non-growing tumors was 63.95 ± 0.09 years (range of 22 to 88 years). Eleven studies reported M: F ratios in growing versus non-growing tumors [3,4,5,7,9,10,11,13,16,17,22]. In these studies, the M: F ratio in patients with growing tumors was 33:143 with males comprising 18.75% of the population with growing meningiomas.…”
Section: Results:-mentioning
confidence: 97%
“…Published reports are often limited by a retrospective study design, small sample size, and short follow-up period. [1][2][3][4][5][6][7][8][9][10][11][12][13][14]16,17,19,[21][22][23] A systematic review and meta-analysis of the studies currently available allows for a better understanding of the natural course of asymptomatic meningiomas, a platform for more research, and a foundation on which a standardized guideline for following these tumors may be built.…”
mentioning
confidence: 99%